Soluble peptidoglycan fragments produced by Limosilactobacillus fermentum with antiproliferative activity are suitable for potential therapeutic development: A preliminary report - Fuochi, Virginia; Spampinato, Mariarita; Distefano, Alfio; Palmigiano, Angelo; Garozzo, Domenico; Zagni, Chiara; Rescifina, Antonio; Li Volti, Giovanni; Furneri, Pio Maria (Frontiers in Molecular Biosciences, 2023)
Currently, the use of probiotic strains and their products represents a promising innovative approach as an antagonist treatment against many human diseases. Previous studies showed that a strain of Limosilactobacillus fermentum (LAC92), previously defined as Lactobacillus fermentum exhibited a suitable amensalistic property. The present study aimed to purify the active components from LAC92 to evaluate the biological properties of soluble peptidoglycan fragments (SPFs). Cell-free supernatant (CFS) and bacterial cells were separated after 48 h of growth in MRS medium broth and treated for the isolation of the SPFs. Antimicrobial activity and proliferation analysis on human cell line HTC116 were performed using technologies such as xCELLigence, count and viability, and clonogenic analysis. MALDI MS investigation and docking analysis were performed to determine molecular structure and hypothetical mode of action, respectively. Our results showed that the antimicrobial activity was mainly due to SPFs. Moreover, the results obtained investigating the SPFs effect on the cell line HCT116 showed substantial preliminary evidence suggesting their significant cytostatic and quite antiproliferative properties. Although MALDI was unable to identify the molecular structure, it was subsequently revealed by analysis of the bacterial genome. The amino acid structure was called peptide 92. Furthermore, we confirmed by molecular docking studies the interaction of peptide 92 with MDM2 protein, the negative regulator of p53. This study showed that SPFs from the LAC92 strain exerted anticancer effects on a human colon cancer HCT116 cell line via antiproliferation and inducing apoptosis. These findings indicated that this probiotic strain might be a potential candidate for applications in functional products in the future. Further examination is needed to understand the specific advantages of this probiotic strain and improve its functional features to confirm these data. Moreover, deeper research on peptide 92 could increase our knowledge to understand if it will be possible its application to specific diseases such as CRC.